2018
DOI: 10.21873/anticanres.12253
|View full text |Cite
|
Sign up to set email alerts
|

Re-irradiation with 36 Gy (1.5 Gy Twice Daily) Plus Paclitaxel for Advanced Recurrent and Previously Irradiated SCCHN is Feasible

Abstract: Abstract. Background About half the patients who were treated for advanced nonmetastatic squamous cell carcinoma of the head and neck (SCCHN) develop a loco-regional recurrence either at the primary tumor site and/or in regional lymph nodes (1-3). In case of such a recurrence, a complete resection is often not safely possible, and the patients are referred to radiotherapy, ideally combined with concurrent chemotherapy (4). However, many of these patients had already received 60-70 Gy of radiotherapy (usually w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Toxicity didn’t exceed grade 2 [ 79 ]. Rades et al [ 80 , 81 ] reported that using lower dose ranging from 36 to 44.4 Gy concurrent with paclitaxel, four of 6 patients survived over 12 months after re-irradiation. Only 1/6 patient developed into grade 3 toxicity.…”
Section: Hyperfraction Radiotherapymentioning
confidence: 99%
“…Toxicity didn’t exceed grade 2 [ 79 ]. Rades et al [ 80 , 81 ] reported that using lower dose ranging from 36 to 44.4 Gy concurrent with paclitaxel, four of 6 patients survived over 12 months after re-irradiation. Only 1/6 patient developed into grade 3 toxicity.…”
Section: Hyperfraction Radiotherapymentioning
confidence: 99%